1996
DOI: 10.1007/bf00041385
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of a napin gene promoter: identification of promoter elements required for embryo and endosperm-specific transcription

Abstract: The promoter region (-309 to +44) of the Brassica napus storage protein gene napA was studied in transgenic tobacco by successive 5' as well as internal deletions fused to the reporter gene GUS (beta-glucuronidase). The expression in the two main tissues of the seed, the endosperm and the embryo, was shown to be differentially regulated. This tissue-specific regulation within the seed was found to affect the developmental expression during seed development. The region between -309 to -152, which has a large ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 41 publications
5
84
0
2
Order By: Relevance
“…studies revealed that wild-type and the mutant napA promoters, including 21101 (D1), 2309 (D2), 2211 (D7), and 2152 (D8), showed a similar expression pattern at different developmental stages of embryogenesis in the transgenic tobacco plants, although the expression level of the mutant promoters varied significantly. The promoter reporter constructs had barely detectable expression 5 to 10 d after pollination (DAP; globule to heart stages), followed by significant expression at 10 to 15 DAP (heart to torpedo stages), and reached the highest expression level 30 DAP (Stålberg et al, 1993;Ellerströ m et al, 1996). Consistent with these results, expression of D7:BnL1L (see below) in the transgenic Arabidopsis embryos was detectable around 7 to 10 DAP and had a higher expression level at 13 DAP (Supplemental Fig.…”
Section: Modification and Characterization Of Seed-specific Promoterssupporting
confidence: 71%
See 1 more Smart Citation
“…studies revealed that wild-type and the mutant napA promoters, including 21101 (D1), 2309 (D2), 2211 (D7), and 2152 (D8), showed a similar expression pattern at different developmental stages of embryogenesis in the transgenic tobacco plants, although the expression level of the mutant promoters varied significantly. The promoter reporter constructs had barely detectable expression 5 to 10 d after pollination (DAP; globule to heart stages), followed by significant expression at 10 to 15 DAP (heart to torpedo stages), and reached the highest expression level 30 DAP (Stålberg et al, 1993;Ellerströ m et al, 1996). Consistent with these results, expression of D7:BnL1L (see below) in the transgenic Arabidopsis embryos was detectable around 7 to 10 DAP and had a higher expression level at 13 DAP (Supplemental Fig.…”
Section: Modification and Characterization Of Seed-specific Promoterssupporting
confidence: 71%
“…Previous studies on the napA promoter indicated that the sequences between 2152 and +44 are essential for the seed-specific expression pattern in transgenic tobacco plants, and several ciselements upstream from 2152 were found to act as positive or negative regulatory motifs (Stålberg et al, 1993;Ellerströ m et al, 1996). We made similar napA promoter GUS reporter constructs that were stably transformed into Arabidopsis plants.…”
Section: Modification and Characterization Of Seed-specific Promotersmentioning
confidence: 99%
“…Evolutionary fate of rhizome-specific genes transcription (Ellerstrom et al, 1996), also showed lower frequencies in the promoter regions of S. bicolor and O. sativa than S. propinquum. Another possibility for partial loss of subfunctions of the RT-enriched genes in domesticated genotypes would be that an alternative splice form with rhizomespecificity is lost but the other form(s) still remain due to their importance in other organs.…”
Section: Discussionmentioning
confidence: 93%
“…Five additional cis-acting regulatory elements, such as CRT/DRE motif (Xue, 2003), (CA) n element in storage protein genes (Ellerstrom et al, 1996), TATA box (Grace et al, 2004), the CCA1-binding element related to regulation by phytochrome (Wang et al, 1997), and pyrimidine box required for gibberellic acid (GA) induction (Cercos et al, 1999), were also more abundant in S. propinquum than either S. bicolor or O. sativa alleles (Table 3).…”
Section: Evolutionary Fate Of Rhizome-specific Genesmentioning
confidence: 99%
“…Napin is expressed specifically in the whole embryo and in fully developed seeds, and no apparent difference is seen in its expression within the embryo (Ellerström et al, 1996). However, there are differences during seed development.…”
Section: Spatial Distribution Of Lipidsmentioning
confidence: 98%